2019
DOI: 10.1016/j.heliyon.2019.e01710
|View full text |Cite
|
Sign up to set email alerts
|

Thiamine and benfotiamine protect neuroblastoma cells against paraquat and β-amyloid toxicity by a coenzyme-independent mechanism

Abstract: Background Benfotiamine (BFT) is a synthetic thiamine precursor with high bioavailability. It is efficient in treating complications of type 2 diabetes and has beneficial effects in mouse models of neurodegenerative diseases. The mechanism of action of BFT remains unknown, though it is sometimes suggested that it may be linked to increased thiamine diphosphate (ThDP) coenzyme function. Methods We used a mouse neuroblastoma cell line (Neuro2a) grown in thiamine-restricte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(44 citation statements)
references
References 39 publications
(70 reference statements)
3
31
0
1
Order By: Relevance
“…Thiamine also regulates activities of enzyme like malate dehydrogenase and glutamate dehydrogenase [71]. Thiamine can act as an antioxidant [13] [19,26,72,73] and may act directly in cholinergic transmission [74]. Thiamine serves as an allosteric regulator of many proteins [73].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thiamine also regulates activities of enzyme like malate dehydrogenase and glutamate dehydrogenase [71]. Thiamine can act as an antioxidant [13] [19,26,72,73] and may act directly in cholinergic transmission [74]. Thiamine serves as an allosteric regulator of many proteins [73].…”
Section: Discussionmentioning
confidence: 99%
“…In animal models of amyloid plaque formation, benfotiamine reduces amyloid plaque numbers and phosphorylated tau levels, elevates the phosphorylation of glycogen synthase kinase-3α and -3β, and improves memory [31]. In other animal models, benfotiamine modulates activation of GSK3-β [32], restores neurogenesis [26,33], modulates AMPA receptor expression [25] and decreases oxidative stress [26]. Together, these results suggest that benfotiamine may be therapeutically beneficial for AD.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Charao et al have shown significant antioxidant property of melatonin in paraquat poisoning [13]. The oxidative injuries of paraquat have also been demonstrated due to its chronic exposure [14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…For this reason, we chose thiamine as a new pharmacological way for the management of excessive aggression, induced by ultrasound stress, which was shown to be associated with oxidative stress and inflammation Costa-Nunes et al, in press) (Chapter 2, Chapter 3). We also tested benfotiamine, a synthetic thiamine precursor, which dephosphorylation product S-benzoylthiamine has high lipid solubility, that facilitates permeation in cell membranes (Sambon et al, 2019). As a result, it allows for higher levels of thiamine in the brain, and thus we expected it to be more effective than thiamine in preventing stress-induced aggression and other behavioral and molecular changes.…”
Section: Altered Internalization and Expression Of Ampa Receptor Subumentioning
confidence: 99%